Foundations of Ajax - Schutta, Nathaniel; Asleson, Ryan (Apress : Imprint: Apress, 2006)
Ajax burst onto the Web development scene by offering highly interactive, desktop-like Web applications that can be deployed through any modern Web browser without the need for special plug-ins. Ajax is built on existing Web technologies such as JavaScript, HTML, and CSS, and it is used in conjunction with your favorite server-side language. Foundations of Ajax explains how to combine these technologies effectively to implement Ajax into your new or existing Web applications. Like you, we are developers who are in the trenches, tasked with building Web-enabled applications that provide real value to our customers. As the Web continues to grow, the demand for more expressive and engaging interfaces will continue to increase. Much of the early hype surrounding Ajax centered on its use by Internet powerhouses such as Google and Amazon. However, just because the initial forays into Ajax were pioneered by leading software development firms doesn't mean your application wouldn't also benefit from these techniques. You already know how to develop Web applications, so this book uses specific, focused examples to teach the Ajax tools and techniques you'll need to bring your applications to life. Armed with this book and your existing development expertise, you too will be able to apply Ajax techniques to your application to enrich the end users experience. When we first saw the potential of Ajax, we knew we had to start leveraging it for our own applications. Along the way weve learned some hard-earned knowledge that we thought needed to be shared with the rest of the development community. With this book, you'll be able to easily extend your own applications with Ajax and have fun while doing it. We hope that someday well be reading about your great Ajax-enabled application!